The Relationship of Self Efficacy with Burnout Syndrome in Nursing Professional Students - Damayanti, Rizka Dwi; Qowi, Nurul Hikmatul; Ubudiyah, Masunatul (Jurnal Surya, 2023)
Introduction: Burnout is a major problem for students as they face a variety of academic, social, and personal challenges. Burnout can cause negative behavior in students such as unreal in doing coursework, negative expression, not attending lectures, low motivation, dropping out and so on. The purpose of this study was to determine the relationship between self-efficacy and Burnout in professional studentsMethods: This study used a correlational analytical design with a cross sectional approach using the Simple Random Sampling (SRS) Technique, 89 respondents were obtained. The study data were taken using the General Self Efficacy Scale questionnaire. to measure self-efficacy and the Maslach Burnout Inventory questionnaire to measure Burnout.  Data analysis using Spearman rhoResults: 82% of students had moderate self-efficacy and 73% had moderate burnout. The spearmans rho test showed indigo p = 0.609 with RS = -0.055, which means that there was no significant relationship between self-efficacy and Burnout in ners professional studentsConclusion: The results showed that the high and low Self Efficacy of professional students will not affect the level of student burnoutKeywords: Self Efficcay, Burnout, Nursing Students